TAXATION AND COMPETITIVENESS IN THE SERVICE SECTOR IN THE TRI-BORDER AREA: A COMPARATIVE ANALYSIS BETWEEN BRAZIL, PARAGUAY, AND ARGENTINA - Taves, Ed Ernest; Mendonça, Thiago Hokai; Souza, Leonor Venson de; Silva, Alvaro Antônio da (Seven Editora, 2026)
Differences in tax and labor systems among neighboring countries play a strategic role in border regions, where business mobility is high and competitiveness is strongly affected by operational costs. In this context, taxation of the service sector becomes a decisive factor for the attraction or relocation of economic activities. This study provides a comparative analysis of taxation applied to the service sector in the Triple Frontier region, comprising Brazil, Paraguay, and Argentina, based on legislation in force in 2025. The research adopts a descriptive and comparative approach, supported by documentary and bibliographic analysis, focusing on taxes levied on revenue, income, and payroll, as well as mandatory labor charges. The results reveal significant tax asymmetries among the countries, highlighting the high tax burden and regulatory complexity of the Brazilian and Argentine systems, in contrast to the Paraguayan model, which is characterized by a simpler and less burdensome structure. The study concludes that differences in tax and labor systems directly affect regional competitiveness, influencing business location and operational decisions in the service sector within the Triple Frontier.DOI: https://doi.org/10.56238/sevened2026.008-004